Dynamics of Firm Size: Moderation Analysis of Profitability and Capital Structure in Assessing Firm Value - Suwandi, Suwandi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Investors often have difficulty making careful investment policies, because they must first evaluate the company's prospects for future growth. This causal research is intended to show the extent to which profitability and capital structure can strengthen firm value through moderating firm size variables in automotive and component companies in the Indonesian capital market in 2018-2022. This study involved 12 companies determined based on a purposive sampling approach. The information for this study stems from the financial reports of the sample entities which were collected by browsing the website www.idx.co.id using a documentation approach. Furthermore, multiple linear regression techniques were applied in analyzing research data. Research reveals that firm value can be influenced by profitability and capital structure positively and significantly, while firm size has the opposite impact. However, firm size does not affect the relationship between capital structure and firm value; rather, it influences the relationship between profitability and firm value. Increasing profitability and improving capital structure are necessary to follow up on the research's composition and ensure that firm value keeps rising.